Tuberculous Pericarditis. Issue 12 (22nd September 2015) - Lin, Hsin-Chia; Lu, Chun-Wei; Lin, Mong-Wei; Chen, Shy-Jye; Wang, Jou-Kou; Wu, Mei-Hwan; Chiu, Sheunn-Nan
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.